1986
DOI: 10.1016/0004-6981(86)90158-7
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of SOx, NOx and aerosol species on Bermuda

Abstract: During August 1982 and January and February 1983, General Motors Research Laboratories operated an air monitoring site on the southwest coast of Bermuda The data show that the levels of the NO, and SO, species reaching Bermuda are determined by the direction of the air flow. The highest levels ofsulfate (mean = 4.0~gm-'), nitric acid (126ppt) and other species are observed when air masses arrive from the northeastern United States while the lowest Jevels (sulfate = 1.1 pgme3; nitric acid = 41 ppt) occur during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(30 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…As in our previous studies (Siak et al, 1985;Wolff et al, 1986a), the polar fractions (Fr 1-4) dominate the mutagenicity and account for more than 70% of the direct-acting mutagenic activity whch is comparable to 64% in the 1981 Detroit samples. In both studies, fraction 2 has the single largest fraction accounting for 34% of the activity in the 1981 Detroit samples and 36% of the activity from the 1985 Warren samples.…”
Section: Mutagenicity Profiles During the Episodessupporting
confidence: 80%
“…As in our previous studies (Siak et al, 1985;Wolff et al, 1986a), the polar fractions (Fr 1-4) dominate the mutagenicity and account for more than 70% of the direct-acting mutagenic activity whch is comparable to 64% in the 1981 Detroit samples. In both studies, fraction 2 has the single largest fraction accounting for 34% of the activity in the 1981 Detroit samples and 36% of the activity from the 1985 Warren samples.…”
Section: Mutagenicity Profiles During the Episodessupporting
confidence: 80%
“…Liousse et al (1996) and Chung and Seinfeld (2002) are depicted by open squares and closed diamonds, respectively. Measurements taken from: Hidy et al, 1974;Hoffmann and Duce, 1974;1977;Ketseridis et al, 1976;Chesselet et al, 1981;Andreae, 1982;1983;Andreae et al, 1984;Dzubay et al, 1984;Ohta and Okita, 1984;Cachier et al, 1986;1990;1994;Japar et al, 1986;Wolff et al, 1986;Clarke, 1989;Mukai et al, 1990;Novakov and Penner, 1993;Chow et al, 1994;Liousse et al, 1996;Novakov et al, 1997;Castro et al, 1999;MolnĆ”r et al, 1999;Kim et al, 2000;Puxbaum et al, 2000. (b) Comparison of OC calculations in case S1.8 with observations.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous line shows the 1:1 relationship between model results and measurements. Measurements taken from: Andreae et al, 1984;Dzubay et al, 1984;Ohta and Okita, 1984;Cachier et al, 1986;1990;1994;Japar et al, 1986;Wolff et al, 1986;Hansen et al, 1988;Noone and Clarke, 1988;Clarke, 1989;Mukai et al, 1990;Heintzenberg and Bigg, 1990;Jennings and O'Dowd, 1990;Hopper et al, 1991;Yaaqub et al, 1991;Jennings et al, 1993;Polissar, 1993;Raunemaa et al, 1993;1994;Chow et al, 1994;Heintzenberg and Leck, 1994;Bodhaine, 1995;Berner et al, 1996;Liousse et al, 1996;Lowe et al, 1996;Pio et al, 1996;Bahrmann and Saxena, 1998;Wolff and Cachier, 1998;Bizjak et al, 1999;Castro et al, 1999;ChĆ½lek et al, 1999;Hitzenberger et al, 1999;Zappoli et al, 1999;Kaneyasu and Murayama, 2000;Kim et al, 2000;Novakov et al, 2000;Puxbaum et al, 2000. …”
Section: Comparison With Measurementsmentioning
confidence: 99%
“…Wolff et al (1986) found that the concentrations and composition of fine aerosol and trace gaseous species on Bermuda in August, 1982 andFebruary, 1983 were governed by the type of air mass influencing the island. During incursions of air from the northeastern United States, which were most frequent during the winter, higher concentrations of the anthropogenically-derived species, such as SO;, HNO,, SO,, 0,, Pb, Se, and elemental carbon were observed relative to air originating in the SE sector.…”
Section: No; the Average Deposition Of No; Tomentioning
confidence: 99%